Managing national security interests amidst military major powers' military engagements - Koirala, Kosh Raj (Unity Journal, 2020)
Existing literatures on the strategic competition between India, China and the US have largely focused on general patterns and trends of their cooperation and engagements in Nepal, including on how China has made its forays in Nepal with its assertive foreign policy overtures since 2008. What has been overlooked, however, is how these three countries are quietly competing with each other to enhance their engagement with the national army. The growing competition among these countries is likely to pose serious challenge to the national army as an institution to exercise its strategic autonomy in its decision making process if some cautions are not exercised in advance. This paper highlights on competing and conflicting interests of major powers to enhance their engagements with the national army in Nepal, and the ways to overcome potential challenges, such military engagements may entail in the future. It also offers a context of the discussion with a brief overview of changing strategic environment in the Asia Pacific in the past 10 years and how Nepal has transformed from a backwater to strategic epicenter for major powers.